Critical Perspective on Faiz’s Biographies - Dr. Sumera Ijaz (Zaban-o-Adab, 2025)
Faiz Ahmed Faiz stands as one of the most revered and celebrated poets of the twentieth century, second only to Allama Iqbal in prominence. A considerable body of work has emerged on his poetry, critical essays, memoirs, letters, and translations into various languages. Alongside these, a notable trend in writing his biographies has also developed. The earliest significant contribution in this regard is that of Ayub Mirza. His book Hum Ke Thehre Ajnabi, published in 1977 during Faiz Sahib’s lifetime, adopts the memoir as its primary narrative form. Later, his subsequent work Faiz Nama came to light, where the elements of memoir and fictional narration are more pronounced, though it also contains the foundational structure of a biography. In the same year, Ashfaq Hussain’s Faiz Ahmed Faiz: Shakhsiyat aur Fan, originally his M.A. thesis, was published. This work was reissued in 2006 with additions and revisions and is notable for its elegance and concise arrangement. In 2002, Ludmila Vasileva authored a book in Russian on Faiz’s life and literary contributions, aimed at Russian students; this was translated into Urdu in 2007 under the title Parwarish-e-Lauh-o-Qalam: Faiz Ahmed Faiz ki Hayat aur Takhleeqat. This biography stands out for its incorporation of new insights and sources from Russian archives. In 2014, Syed Mazhar Jamil produced a comprehensive and voluminous biography titled Zikr-e-Faiz, remarkable for its systematic, well-researched, and fluent narrative. More recently, in 2022, Faiz’s grandson, Dr. Ali Madeeh Hashmi, authored a biography in English, which was later translated into Urdu by Nayer Rabab under the title Baab-e-Saltanat-o-Wafa: Faiz Ahmed Faiz. The distinctive merit of this biography lies in the biographer’s intimate proximity to the subject, which lends a unique authenticity and personal depth to the narrative, unmatched by previous works. In the following article, a critical examination of Faiz’s life and personality will be undertaken through the lens of these major biographical works.